2012
DOI: 10.1177/0960327112444938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc in animal models of anxiety, depression and psychosis

Abstract: The role of zinc (Zn) in anxiety, depression and psychosis was studied in rodents. Zn was administered at doses of 15 and 20 mg/kg intraperitoneally for 7 days. Both doses of Zn reduced the immobility time and increased the swimming time in the modified forced swim test. In the elevated plus maze test, increases in the number of open arm entries and time spent in the open arms were observed with both doses of Zn. In the amphetamine (1 and 2 mg/kg subcutaneously) induced locomotor activity test both doses of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
(40 reference statements)
1
7
0
2
Order By: Relevance
“…Interestingly, MTLE + P patients taking haloperidol showed increased expression of MT-I/II in the inner molecular layer. In the amphetamine animal model of schizophrenia, zinc administration is able to revert behavioral equivalents of positive symptoms [55], but it is unknown if systemic zinc administration alters hippocampal zinc and/or MT-I/II expression. In fact, zinc is a ligand of the haloperidol-sensitive sigma 2 receptor in the mossy fiber of rats [56], suggesting that an increased MT-I/II expression in the mossy fiber of MTLE + P patients would facilitate zinc chelation and proper haloperidol binding.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MTLE + P patients taking haloperidol showed increased expression of MT-I/II in the inner molecular layer. In the amphetamine animal model of schizophrenia, zinc administration is able to revert behavioral equivalents of positive symptoms [55], but it is unknown if systemic zinc administration alters hippocampal zinc and/or MT-I/II expression. In fact, zinc is a ligand of the haloperidol-sensitive sigma 2 receptor in the mossy fiber of rats [56], suggesting that an increased MT-I/II expression in the mossy fiber of MTLE + P patients would facilitate zinc chelation and proper haloperidol binding.…”
Section: Discussionmentioning
confidence: 99%
“…In using the EPM to predict the potential anxiolytic activity of Zn hydroaspartate in rats and mice (Partyka et al, 2011) found an increase in the percentage of open arms entries in both species without significantly altering the length of stay in these arms. Zn chloride at different doses of Zn (15 and 20 mg/kg) promoted anxiolytic effects in supplemented rats, evidenced by the increase in the residence time and the greater number of open arms entries in the EPM (Joshi et al, 2012). Zn oxide supplementation at different doses (5 mg/kg and 10 mg/kg) resulted in an anxiolytic effect in the EPM test in rats (Torabi et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Different Zn compounds such as oxides, hydroaspartate, chloride were intraperitoneally administered at varying doses (Joshi et al, 2012;Torabi et al, 2013;Satała et al, 2016) to test antidepressant properties in several behavioral tests, suggesting that Zn may potentiate the action of antidepressants, in addition to reducing their side effects so that their supplementation has a therapeutic effect (Siwek et al, 2010;Ranjbar et al, 2013). Zn sulfate and gluconate are the most common compounds administered orally (Capdor et al, 2013;Roohani et al, 2013), with the choice of this route being important in T1DM since patients already use injectable insulin.…”
Section: Introductionmentioning
confidence: 99%
“…İntraperitoneyal çinko enjeksiyonunun anhedoniyi azalttığı, diyetle alınan çinko takviyesinin de kognisyon ve davranış üzerine pozitif etkisinin olduğu ortaya konmuştur (15). Yine başka bir hayvan modelinde de çinko takviyesinin anksiyete, depresyon ve psikoz tedavisinde ek tedavi olarak etkili olabileceği gösterilmiştir (16). Şimdiye kadar yapılmış birçok çalışmada çinko eksikliğinin çoklu nörokognitif bozukluklara yol açabileceği vurgulanmış ve çinko takviyesi ile bulgularda düzelme olduğu gösterilmiştir.…”
Section: Discussionunclassified